Persepsi Anggota Potensial terhadap Bauran Pemasaran 7P CSA Tani Sauyunan - Sadeli, Agriani Hermita; Maharani, Nindya Kintan; Agustiar, Gilang; Alwasilah, Mentari Qorina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The transformation of the food system towards sustainability is crucial in the face of the climate crisis, environmental degradation, and social inequality. One approach that promotes sustainable food consumption is Community Supported Agriculture (CSA). This study aims to analyze the influence of the marketing mix on the purchase intention of potential members of CSA Tani Sauyunan, a social urban farming program by Seni Tani in Bandung. Despite the increase in organic product consumption, the number of active CSA consumers remains relatively low. This research uses a quantitative approach through a survey questionnaire targeting Instagram followers of Seni Tani who have never been CSA members. The research instrument employs a 7-point Likert scale to measure perceptions of the seven elements of the marketing mix and purchase intention. The results indicate that the product, process, and physical evidence elements received positive evaluations, reflecting CSA's service quality. However, perceptions of the price element remain low, indicating a mismatch between the value received and the price set. The regression analysis shows that the overall marketing mix affects purchase intention. Therefore, the improvement of the marketing mix 7P strategy is needed to increase purchase intention.